Short Communication: Spiders of Sabah: Fifty new records including the description of a new Leucauge species - DZULHELMI MUHAMMAD NASIR; WONG CHUN XING; ASRAF BAKRI; FASZLY RAHIM; NORMA RASHID YUSOFF (Society for Indonesian Biodiversity, 2016)
Nasir DM, Wong CX, Bakri A, Rahim F, Yusoff NR. 2016. Short Communication: Spiders of Sabah: Fifty new records including the description of a new Leucauge species. Biodiversitas 17: 799-807. This paper is the second part of a continuing series, with the main objective of compiling and recording the spider species that can be found in Sabah, Malaysia. Based on the specimens collected during this field trip, a total of 50 new records of spider species from 11 families and 37 genera have been found. This includes one newly discovered spider species, the Leucauge sabahan sp. nov which is described based on a female specimen. It is hoped that this inventory can be used to assist in the knowledge about the spider species for this stage. In summary, an increment of 18% from the total number of spider species has contributed to a total of 272 recognized spider species recorded in Sabah, Malaysia.Keywords: Araneae, checklist, diversity, distribution, Borneo